Lidocaine infusion with enhanced recovery program protocol for pancreatic cancer surgery: effect on postoperative pain and patient immunity - Alaa Elsayed Ghoneim; Emad Abdelmoneim Arida; Sahar Ahmed El-Karadawy; Ashraf Arafat Abdelhalim; Mohamed Samir Kamel; Wessam Zakaria EL-Amrawy (Alexandria Journal of Medicine)
Background Enhanced Recovery After Surgery (ERAS) has been established in various surgical specialties. This prospective controlled randomized study was intended to assess the efficacy of implementing intravenous lidocaine infusion with enhanced recovery after pancreatic surgery (ERAPS) program on postoperative patients’ outcomes.Methods Thirty patients aged 30 to 70 years, of ASA class II who underwent elective pancreatic cancer surgery under general anesthesia were divided into two equal groups, Group L received IV lidocaine infusion, and Group S received IV saline. Postoperative pain intensity was our primary outcome, total postoperative epidural bupivacaine consumption, hospital stay, gastro-intestinal recovery, time to first ambulation, hospital stay duration, effect on immune response and perioperative complications were secondary outcomes.Results The visual analog scale (VAS) scores for pain were significantly lower in Group L compared with those in Groups S (p < 0.05). Post-operative epidural bupivacaine consumption, time to first patient ambulation, food intake and return of bowel movement were significantly less in Group L (p < 0.05%). There were no significant differences between groups in times to pass first flatus, first defecation, length of hospital stay (p > 0.05). Natural killer cell isolation and cytotoxic lymphocytes count decreased in both studied groups postoperatively in comparison to preoperative value and this reduction was significantly detected in Group S when compared with Group L (p = 0.001). The function of natural killer cell and cytotoxic lymphocytes with or without stimulation enhanced in Group L while it suppressed in Group S postoperatively in comparison to preoperative reading and significant difference was recorded between the two groups (p = 0.001).Conclusion Implementation of lidocaine in ERAS protocol in patients with cancer pancreas undergoing pancreatic surgery decreased pain score, reduced post-operative epidural bupivacaine consumption, shortened time to return of bowel sound, and enhanced patient ambulation and the patient’s immunity.